2021
DOI: 10.3389/fonc.2021.667904
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Profiling of Five Immune-Related lncRNAs for a Prognostic Model of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC), one of the most common tumors worldwide, has the fifth highest mortality rate, which is increasing every year. At present, many studies have revealed that immunotherapy has an important effect on many malignant tumors. The main purpose of our research was to verify and establish a new immune-related lncRNA model and to explore the potential immune mechanisms. We analysed the pathways and mechanisms of immune-related lncRNAs by bioinformatics analysis, screened key lncRNAs based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…AL137782.1 and AC073896.3 are protective factors for colon cancer, which is consistent with our study [38]. Recently, AC099850.3 was proven to be involved in the migration and proliferation of hepatocellular carcinoma by regulating the expression of cell-cycle-related molecules [39]. In addition, AC099850.3was highly expressed in HCC and squamous cell carcinoma of the tongue and increased the predicted value of the signature through coexpression and the ceRNA mechanism [40][41][42][43].…”
Section: Discussionsupporting
confidence: 88%
“…AL137782.1 and AC073896.3 are protective factors for colon cancer, which is consistent with our study [38]. Recently, AC099850.3 was proven to be involved in the migration and proliferation of hepatocellular carcinoma by regulating the expression of cell-cycle-related molecules [39]. In addition, AC099850.3was highly expressed in HCC and squamous cell carcinoma of the tongue and increased the predicted value of the signature through coexpression and the ceRNA mechanism [40][41][42][43].…”
Section: Discussionsupporting
confidence: 88%
“…We conducted univariate, LASSO, and multivariate Cox regression analyses and identified seven NRlncRNAs (AC026355.2, AC099850.3, AF131215.5, UST-AS2, ARHGAP26-AS1, FAM83A-AS1, and AC010999.2) significantly linked to the OS of LUAD patients to construct the necroptosis-related lncRNA signature. Among those lncRNAs, AC099850.3 has been reported to be highly expressed in tumors and closely related to the development and procession of NSCLC ( Zhou et al, 2021 ); AC099850.3 is demonstrated to promote proliferation and migration in hepatocellular carcinoma and is also an important member of the prognosis model in hepatocellular carcinoma and colorectal cancer ( Wu et al, 2021 ; Zhang et al, 2021 ). AF131215.5 also represented the independent prognostic significance of OS in patients with LUAD ( Hou and Yao, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, lncRNA PSMB1 is the first to be found in cancers, while AC129492.1 and AC037459.4 have been reported in other cancers. For instance, AC129492.1 is associated with the prognosis of hepatocellular carcinoma and may regulate immune response in hepatocellular carcinoma [ 24 ]. Moreover, Yin et al also found that AC129492.1 can affect the prognosis in colon cancer and may be involved in the regulation of genome instability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%